CRISPR–Cas systems against carbapenem resistance: from proof-of-concept to clinical translation - Tsolakidou, Pandora Jim (Frontiers in Microbiology, 2025)
Carbapenem-resistant Enterobacterales (CRE) pose a major global threat, driven by plasmid-borne carbapenemase genes such as blaKPC, blaNDM and blaOXA-48. CRISPR–Cas systems offer programmable strategies to selectively eliminate these resistance determinants. This mini-review summarizes recent advances in Cas9-based plasmid curing, RNA-targeting approaches such as Cas13a and Cas13d, and DNA-targeting Cas3-enhanced bacteriophage therapeutics that have entered early clinical evaluation. Particular attention is given to conjugative CRISPR–Cas9 plasmid systems, which enable targeted plasmid eradication without laboratory transformation and broaden the delivery toolbox beyond phage vectors. We further discuss major translational challenges, including delivery efficiency, phage host-range constraints, ecological risks of horizontal CRISPR dissemination, and off-target effects. Finally, we highlight emerging delivery platforms—outer membrane vesicles, lipid and polymeric nanoparticles, conjugative plasmids with containment circuits, and engineered live biotherapeutics—that may complement or overcome current limitations. Collectively, these developments illustrate the potential of CRISPR-based antimicrobials to augment traditional therapies through precise gene-level suppression of carbapenem resistance.